The Impact of Macroeconomics Factors on Real Exchange Rate in Latin America:: A Dynamic Panel Data Analysis - Chávez, Carlos Cesar (Latin American Journal of Trade Policy, 2020)
This paper studies the determinants of the real exchange rate using macroeconomic variables, and whether they can predict it. A panel data is used, which estimator is system GMM that allows controlling the endogeneity of the variables. In turn, we transformed the variables with forward orthogonal deviations (FOD) and first difference (FD), which allows us to eliminate unobserved effects that are invariant in time. To check the robustness of the estimates, different periods were used, from 1980-2019, 2000-2019 and 2010-2019. For the period 1980-2019, it is found that the past values of the real exchange rate, the current values of inflation, economic growth, fiscal and monetary policy have positive effects on the current values of the real exchange rate, while the money supply and the terms of trade have negative impacts on the real exchange rate. For the period 2000-2019, we had similar results and for the period 2010-2019, we found that economic growth has negative impacts on the real exchange rate. It is also presented the Arellano-Bond test and the Sargan test to estimate model over-identification. Using the Pedroni test, we estimated the cointegration of the variables with respect to the real exchange rate, finding cointegration with inflation in the long run. The originality of this paper is that we focused on Latin American countries, analyzing short-term relationships with the System GMM estimator and long-term relationships with the Pedroni Test.